Moral Education as a Foundation for the Formation of Students' Character - Fresyam Antika Ajeng (International Journal of Islamic Educational Research, 2024)
Moral education has a very important role in shaping the character of students. In the context of education, morals include moral and ethical values ​​that form the basis of individual behavior and character. The main aim of moral education is to develop students' personalities who have integrity, civility and responsibility. The process of character formation through moral education involves various aspects, such as instilling the values ​​of honesty, discipline, respect and social responsibility. Apart from that, moral education also plays a role in forming attitudes of tolerance and empathy towards others. Implementation of moral education in schools can be done through various methods, including integration in the curriculum, extracurricular activities, and example from educators. With good moral education, it is hoped that students will be able to face life's challenges with a positive and constructive attitude, and become members of society who contribute positively. Therefore, moral education must be a priority in the education system to create a generation with strong character and high morals.